Evaluation of desiccated and deformed diaspores from natural building materials - Henn, Tamás; Pál, Róbert W. (Ethnobiology Letters, 2015)
With the increasing sophistication of paleoethnobotanical methods, it is now possible to reconstruct new aspects of the day-to-day life of past peoples, and, ultimately, gain information about their cultivated plants, land-use practices, architecture, diet, and trade. Reliable identification of plant remains, however, remains essential to the study of paleoethnobotany, and there is still much to learn about precise identification. This paper describes and evaluates the most frequent types of deformed desiccated diaspores revealed from adobe bricks used in buildings in Southwestern Hungary that were built primarily between 1850 and 1950. A total of 24,634 diaspores were recovered from 333.05 kg adobe samples. These seeds and fruits belong to 303 taxa, and the majority were arable and ruderal weed species. A total of 98.97% of the diaspores were identified to species. In other cases, identification was possible only to genus or family (0.93% and 0.10% of diaspores, respectively). Difficulties in identification were caused mainly by morphological changes in the size, shape, color, and surface features of diaspores. Most diaspores were darker in color and significantly smaller than fresh or recently desiccated seeds and fruits. Surface features were often absent or fragmented. The most problematic seeds to identify were those of Centaurea cyanus, Consolida regalis, Scleranthus annuus and Daucus carota ssp. carota, which are discussed in detail. Our research aids archaeobotanists in the identification of desiccated and deformed diaspores.